Training in normobaric hypoxia induces hematological changes that affect iron metabolism and immunity - Nolte, Svenja; Malhan, Deeksha; Klemmer, Anna; Kastner, Tom; Walter, Nico; Fleckenstein, Daniel; Keck, Johannes; Klügel, Simon; Maier, Celina; Gebhardt, Kristina; Stauber, Tobias; Relógio, Angela; et al. (My University, 2025)
Altitude training is a method among endurance athletes to enhance performance via hypoxia-induced adaptations. However, individual responses vary significantly, with some athletes even showing performance decrements. Iron metabolism and immune function may influence these adaptations, as hypoxia-induced erythropoiesis increases systemic iron demand, potentially affecting immune cells reliant on iron. This study investigated the interplay between hematological, iron, and immunological variables under controlled normobaric hypoxia. 15 highly trained athletes participated in a 21-day live-high-train-low training camp in a normobaric altitude house. Blood samples were collected pre- and post-camp and at four intermediate time points to measure hematological variables, iron metabolism variables, and immunological variables. Pre- and post-performance was assessed via VO2max tests. Statistical analyses included paired t-tests, Wilcoxon rank-sum test, Spearman correlations, and Granger causality analysis to explore systemic temporal interactions. VO2max increased significantly (p < 0.05) with large interindividual variability (2.4 ± 3.5 ml/min/kg). Hemoglobin concentration, erythrocytes, and the soluble transferrin receptor (sTfR) showed significant increases over time (p < 0.05), while ferritin peaked early and declined post-camp. Myeloperoxidase and lactoferrin exhibited dynamic correlations with iron variables (p < 0.05), reflecting competition between erythropoiesis and immune function for iron. The structure of the Granger causality network places transferrin in a central role, highlighting iron metabolism as one key regulator of these adaptations. Normobaric hypoxia training induces systemic physiological changes involving hematological, iron, and immune systems. Controlled hypoxic conditions enable detailed exploration of these interactions, providing insights into optimizing altitude training strategies for endurance performance enhancement.
Keywords: ddc:796